Sexual and reproductive health understanding, attitudes and practices in male teenagers. : July-August 2018. Users of UDA Canelones al Este (Archives of Pediatrics of Uruguay, 2020)
Introduction: in the last 10 years, adolescent sexual and reproductive health (SRH) research has mainly focused on women. Male adolescent studies are necessary in order to promote SRH in this population.Objective: determine the SRH male adolescent understanding, attitudes and practices for users of UDA Canelones al Este. Learn about the information sources they use to address their concerns in this matter. Method: cross-sectional descriptive observational survey. Period: July-August 2018. Inclusion criteria: male adolescent users of ASSE who attended a health check-up at the UDA Canelones al Este Clinic. Data source: survey. data analysis: Absolute and relative frequencies for qualitative variables. PSPP Statistics 1.0.1 Program (2018).Results: sixty male adolescents were included in the study. The average age was 15 years of age. They started to have sexual intercourse n = 37; 67.5% before the age of 15. The main sources of information on sexuality and puberty came 35% from relatives and 20% from friends. 56.7% knew about sexually transmitted diseases. Among the best known and most used contraceptive methods was the male condom with 86.7%. 30% of adolescents always used contraceptive methods during intercourse.Conclusions: the results presented in this research show some aspects of male adolescent sexual and reproductive health. They will enable us to devise measures to address and integrate more adolescent males in the health system and thus reduce the presently existing gap with this population.clusions: the results presented in this research show some aspects of male adolescent sexual and reproductive health. They will enable us to devise measures to address and integrate more adolescent males in the health system and thus reduce the presently existing gap with this population.
Keywords: Sexual and reproductive health; Men's health; Adolescent